Antimicrobial Potential of Gorgonian Alcyonium sp. Associated Bacteria Against Human Pathogenic Skin Diseases - Avicenna Wijayanto; Agus Sabdono; Endang Sri Lestari; Mada Triandala Sibero (Journal of Marine Research, 2023)
Skin diseases are common in tropical countries due to microbial pathogens. The use of antibiotics is one of the efforts to treat skin diseases. However, the misuse and overuse of antibiotics can stimulate the emergence of multi-drug resistance (MDR) pathogens. This study focused on obtaining gorgonian-associated bacteria with antimicrobial activity against Cutibacterium acnes, Staphylococcus epidermidis, Malassezia furfur, and Candida albicans. This research procedure includes sampling, isolation, and purification of bacteria, antimicrobial test with agar plug method, morphological characterization, and molecular identification. The study results showed that one isolate of gorgonian-associated bacteria Alcyonium sp. from Seruni Island, Karimunjawa has antimicrobial activity against Cutibacterium acnes, Staphylococcus epidermidis, and Candida albicans. The results of molecular identification showed that isolate SE.4.2 had a similarity of 98.96% with Pseudoalteromonas shioyasakiensis.